Analisis SWOT Dukungan Komunitas Masyarakat: Suatu Solusi Manajemen Kesehatan Jiwa pada Remaja di Indonesia - Tria Pamungkasari; Dety Mulyanti (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this study was to find out the strengths, weaknesses, opportunities and threats of community support as a mental health management solution for adolescents in Indonesia. This study uses a qualitative research approach with descriptive analysis techniques and utilizes SWOT analysis to achieve research objectives. The results of this study include, first, the strengths of community support as a mental health management solution for adolescents in Indonesia is the high population of Indonesian people and the high number of puskesmas operating in Indonesia. Second, the weakness of community support as a mental health management solution for adolescents in Indonesia is the low level of mental health literacy and the low number of health facilities providing mental health services. The three opportunities for community support as a mental health management solution for adolescents in Indonesia are the development of information technology and the development of communication technology. Fourth, threats to community support as a mental health management solution for adolescents in Indonesia are the high use of social media by adolescents and the presence of the Covid-19 pandemic. Then this research also formulates four strategies based on SO, ST, WO and WT.